Teaching Outside the Box: Senior High School Teaching Experiences, Challenges, and Windows of Innovations of Non-Social Science Majors - Branzuela, Marco J.; Ayro, Eufemia C.; Cruz-Vidal, Michaela Jennarine DL. (Future Science / FSH-PH Publications, 2023)
This research examines the experiences of non-social science majors teaching in teaching social science subjects in senior high school. It utilized a mixed-method approach. A survey and an interview were utilized to collect the data. Sixty respondents took the survey to identify their teaching experiences. Five out-of-field social science teachers who were severely challenged were invited to an interview. Results revealed that more female teachers were engaged in out-of-field teaching. Moreover, teachers aged 26-30 are more likely to be assigned to out-of-field teaching. Also, both public and private schools experience the challenge of out-of-field teaching. Most of the teachers engaged in this scenario were non-education graduates. Core subjects under social sciences are the common subjects taught by non-social science majors. The survey reveals the experiences of non-social science majors in their mastery of the subject handled, ability to prepare scholarly learning material, classroom pedagogy/classroom activity, and psychosocial guidance to students for college preparations. It is discovered that non-social science majors always adhere to the challenges posed by out-of-field teaching. However, psychosocial guidance to students for college preparation was the domain that makes it challenging for non-social science majors to overcome. Five themes emerged based on this study; out-of-field teaching experiences, challenges of non-social science majors, coping mechanisms employed by non-social science majors, perception of non-social majors, and roles of school administrators. The COPE approach was devised to aid teachers, school administrators, and the Department of Education to mitigate the challenges posed by out-of-field teaching experiences.